DISHARMONY AND ITS CORRECTION IN PREMATURE OVARIAN INSUFFICIENCY (Journal of Pharmaceutical Negative Results, 2022)
The hormonal status of women with a diagnosis of STUMP, with removal of one ovary and without surgery were prospectively studied. The study of the hormonal background revealed ovarian insufficiency syndrome in women after surgical treatment. Our studies were carried out in the period from 1 month to 3 months, from 4 to 6 months and 7 months to 12 months after the operation. We investigated changes in the level of the main informative hormones FSH, E2, LH, AMH, since the other hormones, such as cortisol, prolactin, progesterone and testosterone in both groups have changed little, with the ovary preserved, the hormone level is somewhat maintained, thanks to the follicular apparatus in it. And in patients of the second group, ovulatory cycles and normalization of the hormonal background gradually approached the previous state after 9-12 months.